Co‐occurring Down syndrome and SUCLA2‐related mitochondrial depletion syndrome. Issue 10 (27th July 2017) - Couser, Natario L.; Marchuk, Daniel S.; Smith, Laurie D.; Arreola, Alexandra; Kaiser‐Rogers, Kathleen A.; Muenzer, Joseph; Pandya, Arti; Gucsavas‐Calikoglu, Muge; Powell, Cynthia M.
Abstract : Mitochondrial DNA depletion syndrome 5 (MIM 612073) is a rare autosomal recessive disorder caused by homozygous or compound heterozygous pathogenic variants in the beta subunit of the succinate‐CoA ligase gene located within the 13q14 band. We describe two siblings of Hispanic descent with SUCLA2 ‐related mitochondrial depletion syndrome (encephalomyopathic form with methylmalonic aciduria); the older sibling is additionally affected with trisomy 21. SUCLA2 sequencing identified homozygous p.Arg284Cys pathogenic variants in both patients. This mutation has previously been identified in four individuals of Italian and Caucasian descent. The older sibling with concomitant disease has a more severe phenotype than what is typically described in patients with either SUCLA2‐ related mitochondrial depletion syndrome or Down syndrome alone. The younger sibling, who has a normal female chromosome complement, is significantly less affected compared to her brother. While the clinical and molecular findings have been reported in about 50 patients affected with a deficiency of succinate‐CoA ligase caused by pathogenic variants in SUCLA2, this report describes the first known individual affected with both a mitochondrial depletion syndrome and trisomy 21.